2018
DOI: 10.1038/s41467-018-06890-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting IFNα to tumor by anti-PD-L1 creates feedforward antitumor responses to overcome checkpoint blockade resistance

Abstract: Many patients remain unresponsive to intensive PD-1/PD-L1 blockade therapy despite the presence of tumor-infiltrating lymphocytes. We propose that impaired innate sensing might limit the complete activation of tumor-specific T cells after PD-1/PD-L1 blockade. Local delivery of type I interferons (IFNs) restores antigen presentation, but upregulates PD-L1, dampening subsequent T-cell activation. Therefore, we armed anti-PD-L1 antibody with IFNα (IFNα-anti-PD-L1) to create feedforward responses. Here, we find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 39 publications
3
58
0
Order By: Relevance
“…Tumor growth inhibition by anti-PD-1 with prior lenvatinib treatment for 1 week was greater than that achieved by anti-PD-1 alone, nontreatment, or nontreatment with prior lenvatinib treatment (S8 Fig). To examine if the response of tumor to lenvatinib was an important component in the response of the tumors to IFN signal activation [23], we divided the mice into two groups according to a mean of tumor sizes after 1 week of lenvatinib treatment: those with relatively lenvatinib-sensitive smaller tumors (LEN-S) and those with relatively larger tumors that were moderately sensitive to lenvatinib (LEN-L). Mice in the LEN-S group that were subsequently treated with anti-PD-1 showed greater tumor reduction than the other treatment groups (S9 Fig).…”
Section: Resultsmentioning
confidence: 99%
“…Tumor growth inhibition by anti-PD-1 with prior lenvatinib treatment for 1 week was greater than that achieved by anti-PD-1 alone, nontreatment, or nontreatment with prior lenvatinib treatment (S8 Fig). To examine if the response of tumor to lenvatinib was an important component in the response of the tumors to IFN signal activation [23], we divided the mice into two groups according to a mean of tumor sizes after 1 week of lenvatinib treatment: those with relatively lenvatinib-sensitive smaller tumors (LEN-S) and those with relatively larger tumors that were moderately sensitive to lenvatinib (LEN-L). Mice in the LEN-S group that were subsequently treated with anti-PD-1 showed greater tumor reduction than the other treatment groups (S9 Fig).…”
Section: Resultsmentioning
confidence: 99%
“…Our study found that high expression of WTAP can reduce T‐cell infiltration and inhibit tumour immunity, which may be supported by the above studies. Liang et al found that IFNs may be an important target for PDL1 immunotherapy, and they also showed that methylation genes are a potential target for this research …”
Section: Discussionmentioning
confidence: 97%
“…In PDAC tumors from patients and KPC mice, we observed that IL-20 expression significantly correlated with PD-L1 expression. In addition, IL-20 upregulated PD-L1 expression via IFN-α, which is an upstream regulator of PD-L1 produced by some types of cancer cells 40 , 55 . Blocking the activity of IFN-α with an antibody attenuated IL-20-induced PD-L1 expression in KPC tumor cells in vitro, indicating that IL-20 mediated PD-L1 upregulation via IFN-α.…”
Section: Discussionmentioning
confidence: 99%